Dietary inflammatory index is related to asthma risk, lung function and systemic inflammation in asthma. Issue 1 (January 2015) - Wood, L. G.; Shivappa, N.; Berthon, B. S.; Gibson, P. G.; Hebert, J. R.
Summary Background Asthma prevalence has increased in recent years, and evidence suggests that diet may be a contributing factor. Increased use of processed foods has led to a decrease in diet quality, which may be creating a pro‐inflammatory environment, thereby leading to the development and/or progression of various chronic inflammatory diseases and conditions. Recently, the dietary inflammatory index (DII) has been developed and validated to assess the inflammatory potential of individual diets. Objective This study aimed to examine the DII in subjects with asthma compared to healthy controls and to relate the DII to asthma risk, lung function and systemic inflammation. Methods Subjects with asthma (n = 99) and healthy controls (n = 61) were recruited. Blood was collected and spirometry was performed. The DII was calculated from food frequency questionnaires administered to study subjects. Results The mean DII score for the asthmatics was higher than the mean DII score for healthy controls (− 1.40 vs. − 1.86, P = 0.04), indicating that their diets were more pro‐inflammatory. For every 1 unit increase in DII score, the odds of having asthma increased by 70% (OR: 1.70, 95% CI: 1.03, 2.14; P = 0.040). FEV1 was significantly associated with DII score (β = − 3.44, 95% CI: − 6.50, − 0.39; P = 0.020), indicating that for every 1 unit increase in DII score, FEV1 decreased by 3.44 times. Furthermore, plasma IL‐6 concentrations were positively associated with DII score (β = 0.13, 95% CI: 0.05, 0.21; P = 0.002). Conclusion and Clinical Relevance As assessed using the DII score, the usual diet consumed by asthmatics in this study was pro‐inflammatory relative to the diet consumed by the healthy controls. The DII score was associated with increased systemic inflammation and lower lung function. Hence, consumption of pro‐inflammatory foods may contribute to worse asthma status, and targeting an improvement in DII in asthmatics, as an indicator of suitable dietary intake, might be a useful strategy for improving clinical outcomes in the disease.